Portfolio Analysis: Performance and Risk Strategies - Suliman, Rwaida Saeed (Journal of Economic, Administrative and Legal Sciences, 2025)
This research addresses the analysis of the impact of economic and psychological factors on the performance of investment portfolios, aiming to provide effective strategies for improving performance and reducing risks. By examining factors such as interest rates, inflation, and economic growth, the study seeks to understand how these elements influence investor decisions and portfolio performance.The research relies on a methodology that reviews current literature and previous studies, using statistical analytical methods to explore the relationship between returns and risks within the context of financial markets.The results showed that economic factors, such as interest rates and inflation, significantly impact investor decisions and investment portfolio performance. It also revealed that the psychological behavior of investors, including emotions and behavioral biases, plays an important role in shaping portfolio construction strategies. The findings emphasized the importance of diversification as a key strategy for enhancing performance and reducing risks.The research concluded that understanding economic and psychological factors is essential for investors to achieve their financial goals. The study highlights the importance of using advanced analytical tools to assess risks and returns, helping investors make informed decisions. Additionally, it recommends enhancing psychological awareness among investors to mitigate the impact of emotions on their investment decisions, thereby contributing to improved performance efficiency in financial markets.
Keywords: performance of investment portfolios; economic factors; financial markets; investor behavior; interest rates